2021
DOI: 10.3390/rs13040588
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of TMPA and IMERG Precipitation Datasets in the Arid Environment of El-Qaa Plain, Sinai

Abstract: The replenishment of aquifers depends mainly on precipitation rates, which is of vital importance for determining water budgets in arid and semi-arid regions. El-Qaa Plain in the Sinai Peninsula is a region that experiences constant population growth. This study compares the performance of two sets of satellite-based data of precipitation and in situ rainfall measurements. The dates selected refer to rainfall events between 2015 and 2018. For this purpose, 0.1° and 0.25° spatial resolution TMPA (Tropical Rainf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…Bearing in mind the above, the suitability of IMERG precipitation datasets was investigated over El-Qaa Plain in the preceding research [14] where the frequency of light events is high. The results of that study were encouraging, as IMERG datasets from the light-intensity events were highly correlated with the in-situ measurements.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Bearing in mind the above, the suitability of IMERG precipitation datasets was investigated over El-Qaa Plain in the preceding research [14] where the frequency of light events is high. The results of that study were encouraging, as IMERG datasets from the light-intensity events were highly correlated with the in-situ measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Over the same region, Morsy et al [14] contrasted TRMM (Tropical Rainfall Measurement Mission) and IMERG satellite precipitation products, on the one hand, and against ground rain gauges, on the other hand. They concluded that IMERG estimations perform better than TRMM.…”
Section: Integrated Multi-satellite Retrievals For Gpm (Imerg)mentioning
confidence: 99%
See 2 more Smart Citations
“…In general, CHIRPS showed slightly better performance than the other three IMERG runs for monthly and seasonal time scales. Previous studies have already confirmed the superiority of CHIRPS than IMERG runs for different parts of the world [40,[71][72][73], including Ethiopia [31,47,49]. For example, Wedajo et al [47] reported better rainfall estimation by CHIRPS compared with IMERG and TAMSAT3 and 3B42/3 products for the Dhidhessa River Basin, Ethiopia.…”
Section: Seasonal Rainfall Evaluationmentioning
confidence: 91%